Professionalizing corporate professions: Professionalization as identity project. Issue 2 (April 2018) - Reed, Cara
Professional bodies have traditionally played a core role in professionalization, setting the ideals for professional identity, knowledge and practice. However, the emergence of corporate professions has problematized the role of the professional body in contemporary professionalization. This article examines the role of the professional body and its ability to resonate with practitioners' professional identity construction through empirical analysis of public relations. The article introduces the concept of professionalization as identity project as another means by which to understand attempts at social closure in emergent corporate professions. For professionalization as identity project to be fully realized, the research suggests the blending of traditional discourses of professionalism with emergent discourses of entrepreneurialism is required. Consequently, the study highlights that corporate professionalization as identity project reflects the contemporary tensions and contradictions between the lived reality and orthodox ideology of 'being a professional'.